Labour Management Relations as a Framework for Industrial Sustainability - Ugoani, John Nkeobuna Nnah (American Journal of Social Sciences and Humanities, 2019)
Work is necessary for the survival of individual employees and labour management relations aim at achieving the collective interests of employers and employees to promote productivity and industrial sustainability. The early Knights of Labour sought to protect the interest of labour as a means of enhancing industrial growth and survival because labour is the major determinant of productivity. In many countries today including Kenya, South-Africa, Norway, Nigeria among others, employees in small and medium enterprises, including most private tertiary institutions are not unionized thereby giving such employees the freedom to use the organizations as a stepping stone for better employment opportunities and at the detriment of industrial growth and sustainability. Since organizations are typically coalitions of interest groups, negotiation between labour and management must always receive great attention as one of the modern methods of achieving industrial harmony. Often negotiation is characterized by divergent views and the role of labour management relations becomes to promote collaboration. 200 participants took part in the study conducted through the survey research design to explain the relationship between labour management relations and industrial sustainability. Analysis through descriptive and correlation methods showed a strong positive relationship between the variables of interest. The study was not exhaustive, and further study should examine the relationship between leadership and performance. It was suggested that the accommodation principle should always be used to achieve industrial harmony and sustainability.